Simulation Study of UAV and Robotic Arm Cooperation Based on Orthogonal Iteration Algorithm - Su, Zihan (International Journal of Computer Science and Information Technology, 2024)
Aiming at the problem of cooperation between quadrotor UAV and six-degree-of-freedom robotic arm in the warehouse environment, the goal is to achieve smooth cooperation to improve logistics efficiency as well as accurate status delivery of goods. Taking the quadrotor UAV and the six-degree-of-freedom robotic arm as the research object, the PID control algorithm is used for the control system design of the UAV, and the D-H parameter method is used to establish the coordinate system of the robotic arm, and the kinematic equations are further derived to carry out the model construction of the robotic arm model and the motion simulation using MATLAB. For the matching process, laser SLAM positioning and navigation simulation is used for the UAV trajectory simulation, monocular colour information acquisition method is used for the docking of the UAV and the robotic arm, orthogonal iteration algorithm is used to complete the positional solution before the UAV receives the goods, and finally the simulation is completed from the trajectory of the UAV approaching the robotic arm to the transfer of the goods from the robotic arm to the end of the UAV actuator. The results show that the robot arm model is correctly constructed, the UAV SLAM trajectory simulation is completed, and the monocular colour information acquisition method and the orthogonal iteration algorithm are effective, which can ensure the correct docking of the UAV end-effector and the gripper jaws of the robot arm. The mechanical arm and UAV can complete the action of transferring goods with the expected motion accuracy, which lays the foundation for the further practical application of UAV.